100 Days Closer to Christ - Graham, William C., 1950- (Book collections on Project MUSE., 2014)
Everyone has have moments of grace in their lives, glimpses of God's presence and God's mystery. The Word made flesh, God-with-us, inspires these moments and sometimes allows seeing and feeling that transformation in grace. In 100 Days Closer to Christ, Father William C. Graham invites readers to consider these moments and experience the transforming presence of God in their lives. These compelling essays invite readers to immersion in joyful hope: dreams, disciplines, and promises; fond embraces and quiet satisfaction; plans and prospects; awe and wonder. The chapters consider moments of grace through encounters that resemble lectio divina, inviting reflections flowing from God's word or the church's life of prayer, giving flashes of insight and meaning on a pilgrim's way. The essays in 100 Days Closer to Christ are meant to inspire thoughtful prayer. Whether they are seasonal or attitudinal, each seeks to stand before Mystery in awe, wonder, praise, and thanksgiving.